An Immunocompetent Case of Capnocytophaga canimorsus Infection Complicated by Secondary Thrombotic Microangiopathy and Disseminated Intravascular Coagulation - Tani, Naoki (Intern Med, 2019)
A 62-year-old woman with no previous history developed a Capnocytophaga canimorsus infection followed by thrombotic microangiopathy (TMA) and disseminated intravascular coagulation (DIC). She was treated with antibiotics and plasma exchange (PE) and recovered. C. canimorsus sepsis sometimes causes not only DIC but also TMA. The mortality of TMA is extremely high, so we should not hesitate to perform PE when a patient shows TMA symptoms.